Functional characterization of two variants in the 3’-untranslated region (UTR) of transcription factor 4 gene and their association with schizophrenia in sib-pairs from multiplex families - Mohamed, Zahra Isnaini; Tee, Shiau Foon; Chow, Tze Jen; Loh, Siew Yim; Yong, Hoi Sen; Bakar, Abdul Kadir Abu; Tang, Pek Yee (Elsevier, 2019)
Transcription factor 4 (TCF4) gene plays an important role in nervous system development and it always associated with the risk of schizophrenia. Since miRNAs regulate targetgenes by binding to 3'UTRs of target mRNAs, the functional variants located in 3′UTR of TCF4 are highly suggested to affect the gene expressions in schizophrenia. To test the hypothesis regarding the effects of the variants located in 3'UTR of TCF4, we conducted an in silico analysis to identify the functional variants and their predicted functions. In this study, we sequenced the 3'UTR of TCF4 in 13 multiplex schizophrenia families and 14 control families. We found two functional variants carried by three unrelated patients. We determined that the C allele of rs1272363 and the TC insert of rs373174214 might suppress post- transcriptional expression. Secondly, we cloned the region that flanked these two variants into a dual luciferase reporter system and compared the luciferase activities between the pmirGLO-TCF4 (control), pmirGLO-TCF4-rs373174214 and pmirGLO-TCF4-rs1273263. Both pmirGLO-TCF4-rs373174214 and pmirGLO-TCF4-rs1273263 caused lower reporter gene activities, as compared to the control. However, only the C allele of rs1272363 reduced the luciferase activity significantly (p = 0.0231). Our results suggested that rs1273263 is a potential regulator of TCF4 expression, and might be associated with schizophrenia. © 2019 Elsevier B.V.